Exchange Rate Determination on the African Continent: A Panel Study on EAC and Comesa Countries - Omol, Charles Aaaron (2017)
Exchange rate is an issue of great importance in international trade, which is seen as a driver of economic growth and development among African countries. This study is investigates the factors responsible for determining exchange rate in a sample of 16 countries selected from the EAC and COMESA regional blocs. The period considered spans from 2006 to 2014 and the variables examined include interest rate, inflation, terms of trade, external debt, national output and political stability. After applying two-step dynamic panel estimation, the results show reveal that terms of trade, external debt, national output and political stability each have a negative significant relationship with exchange rate meaning they positively affect currency value.